IL-34 aggravates myocardial ischemia-reperfusion injury by upregulating the HMGB1-IL-17A-IL-6 axis through the JAK signaling pathway. - Ruisong Ma; Xiaochun Hu; Wenwen Fu; Xiaorong Hu (PLoS ONE)
Interleukin-34 (IL-34) was recently reported to be a new biomarker for atherosclerosis diseases, such as coronary artery disease and vascular dementia. IL-34 regulates the expression of proinflammatory cytokines (IL-17A, IL-1 and IL-6), which are classical cytokines involved in myocardial ischemia‒reperfusion (MI/R) injury. However, the exact role of IL-34 in MI/R remains unknown. In this study, a rat MI/R model was used to explore the effect of IL-34 on modulating inflammatory processes during MI/R injury. First, eighteen rats were subjected to 30 min of LAD ligation followed by 0 h, 1 h, 2 h, 4 h, 8 h or 24 h of reperfusion (n = 3 for each group). The level of IL-34 peaked at 4 h after MI/R in the ischemic myocardium. Next, ischemia for 30min and reperfusion for 4h (I/R) model was used. 24 rats were randomly divided into I/R group (n = 8), IL-34+IR group (n = 8) and IL-34+ab12+IR group (n = 8). We found that IL-34 pretreatment increased the expression of inflammatory cytokines, including high mobility group Box 1 (HMGB1), IL-17A, and IL-6; the expression of the apoptosis protein cleaved caspase-3; and the Bcl-2/Bax ratio within the ischemic myocardium. We also observed increased serum cardiac enzymes and a larger myocardial injury area. Treatment with a Janus kinase (JAK) pathway inhibitor, however, partially reduced the expression of these proteins and attenuated myocardial injury. Together, these results showed that IL-34 aggravates MI/R injury by inducing the expression of the HMGB1-IL-17A-IL-6 axis and apoptosis after MI/R, which is partially dependent on the JAK pathway. Therefore, blocking the JAK signaling pathway or inhibiting IL-34 expression might provide a new idea to reduce MI/R injury, but further researches are needed.